Strategic plan for Bios Dynamis Multi-Purpose Cooperative - Jalipa, Ana Theresa E. (School of Management, University of the Philippines Mindanao, 2011)
This strategic paper presents the possible businesses strategies for Bios Dynamic Multi-Purpose Cooperative (BDMPC). It evaluates the external factors of the organic rice industry and presented the strength and weaknesses of the organization. Pertinent data of this paper was gathered through personal interviews with the management team. Secondary data were also use to support this study. BDMPC is an off-shoot of Don Bosco Foundation for Sustainable Development, Inc. (DBFSDI). It was tasked by DBFSDI to manage the Alternative Marketing Services and Alternative Savings and Credit Services. Its role is to generate income for DBFSDI while the foundation furthers its mission. The arrangement is covered by the Management Service contract with specific revenue sharing provisions between DBFSDI and Bios Dynamic MPC. The Internal Factor Evaluation matrix shows that BDMPC is internally strong. Being the largest producer of organic rice in Mindanao, is one of their strengths. While financial aspect shows promising figures, it is because they are financially dependent with DBFSDI. Liquidity problems surface during harvest time. In addition to that, over supply of palay continues to be a problem. External environment however provides opportunities for them. Given the complexities involve in the organic food industry, BDMPC should find the perfect market niche for their organic rice. The SWOT Matrix and QSPM discloses that the most suitable strategy for BDMPC is market development. Though it may sound very costly but by adding value in a way that attracts a particular kind of customer, they can steadily build the enterprise? success. Proposed strategies include, opening of specialty stores in Manila area where Class A and B are dominant, adding industry buyers who orders volume of rice for their employees. Massive promotion to increase awareness was also suggested. To be able to achieve this, BDMPC should hire a marketing manager to handle all marketing related concerns. With these strategies it is expected to increase sales of organic rice by 50% for 3-5 years inventories are expected to fall by 30% for the years to come.